2021
DOI: 10.3390/su132413715
|View full text |Cite
|
Sign up to set email alerts
|

Satellite Multi/Hyper Spectral HR Sensors for Mapping the Posidonia oceanica in South Mediterranean Islands

Abstract: The Mediterranean basin is a hot spot of climate change where the Posidonia oceanica (L.) Delile (PO) and other seagrasses are under stress due to its effect on marine coastal habitats and the rising influence of anthropogenic activities (i.e., tourism, fishery). The PO and seabed ecosystems, in the coastal environments of Pantelleria and Lampedusa, suffer additional growing impacts from tourism in synergy with specific stress factors due to increasing vessel traffic for supplying potable water and fossil fuel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…And, even using few validation data acquired with years of difference and the lack of knowledge about the optical properties at the moment of image acquisition (to help defining the parameterization range), the model obtained qualitatively good results. Previous studies have showed the potential of PRISMA data for optical bathymetry retrieval (Alevizos et al, 2022), seabed mapping (Borfecchia et al, 2021), and retrieval of water quality parameters in inland waters (Niroumand-Jadidi et al, 2020;Bresciani et al, 2022). Together with the results presented in our present analysis, these studies indicate the potential of the hyperspectral PRISMA sensor for monitoring aquatic systems.…”
Section: Regionsupporting
confidence: 85%
“…And, even using few validation data acquired with years of difference and the lack of knowledge about the optical properties at the moment of image acquisition (to help defining the parameterization range), the model obtained qualitatively good results. Previous studies have showed the potential of PRISMA data for optical bathymetry retrieval (Alevizos et al, 2022), seabed mapping (Borfecchia et al, 2021), and retrieval of water quality parameters in inland waters (Niroumand-Jadidi et al, 2020;Bresciani et al, 2022). Together with the results presented in our present analysis, these studies indicate the potential of the hyperspectral PRISMA sensor for monitoring aquatic systems.…”
Section: Regionsupporting
confidence: 85%
“…During the last decades, several techniques have supported seagrass mapping (Pasqualini et al, 2001), from Multibeam Echo-Sounding, Side Scan Sonar, Laser Imaging Detection and Ranging to panchromatic and multi-spectral data from satellites and Uncrewed Aerial Vehicles (Veettil et al, 2020). In this regard, multi/hyperspectral satellite sensors (i.e., Sentinel 2 MSI and PRISMA) have been successfully tested to monitor the stress level of PO (Borfecchia et al, 2021): time-series imagery exploits high-resolution data, while up-to-date sensors and techniques would allow to achieve even ultra-high resolution also for the time-series. More recently, photogrammetry is also increasingly being used to monitor the state of PO and the outcome of restoration projects, to derive finer-scale measurements with respect to the other geomatics techniques (Rende et al, 2022).…”
Section: State-of-the-artmentioning
confidence: 99%
“…More recently, PRISMA and DLR's Environmental Mapping and Analysis Program (EnMap) are able to measure Earth's surface properties with narrow contiguous spectral bands from VIS to the shortwave infrared (SWIR). In particular, PRISMA, the hyperspectral sensor distributed by the Italian Space Agency (ASI) [15][16][17], has been proven to be able to support water quality studies [12,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%